Advection, moistening, and shallow‐to‐deep convection transitions during the initiation and propagation of Madden‐Julian Oscillation. (11th September 2014) - Hagos, Samson; Feng, Zhe; Landu, Kiranmayi; Long, Charles N.
Abstract Using observations from the 2011 AMIE/DYNAMO field campaign over the Indian Ocean and a high‐resolution regional model simulation, the processes that lead to the rapid shallow‐to‐deep convection transitions associated with the initiation and eastward propagation of the Madden‐Julian Oscillation (MJO) are examined. By tracking the evolution of the depth of several thousand individual model simulated precipitation features, the role of and the processes that control the observed midtropospheric moisture buildup ahead of the detection of deep convection are quantified at large and convection scales. The frequency of shallow‐to‐deep convection transitions is found to be sensitive to this midlevel moisture and large‐scale uplift. This uplift along with the decline of large‐scale drying by equator‐ward advection causes the moisture buildup leading to the initiation of the MJO. Convection scale moisture variability and uplift, and large‐scale zonal advection play secondary roles.